Fallopian tube cancer – analysis of cases and literature review - Szubert, Maria; Suzin, Jacek; Kowalczyk-Amico, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction: Primary fallopian tube cancer (PFTC) is the rarest malignancy of the female genital tract. The unspecific clinical manifestations and its uncommon occurrence make the diagnosis of PFTC difficult. Objectives: To present 3 cases of patients with oviductal cancer and to review the literature. Materials and methods: Retrospective analysis of three cases of oviductal tumours diagnosed in patients of the First Department of Obstetrics and Gynaecology, Medical University of Łódź, in the period 2004-2009. Results: The diagnosis of adenocarcinoma was established in each patient. In one case there was a necessity of histopathological examination using immunohistochemistry methods. Conclusions: The correct diagnosis is usually made after histopathological examinations of tumour masses. There are no differences in signs and symptoms and in physical examinations between ovarian tumour and PFTC.